2014
DOI: 10.1111/1755-6724.12302
|View full text |Cite
|
Sign up to set email alerts
|

The Phototropism of Jurassic Petrified Wood in North China Plate

Abstract: Trees on the side directly exposed to sunlight generally grow faster than on the opposite side, a phenomenon termed plant phototropism. There are in situ vertical trunks of silicified wood in the Xiadelongwan area of Yanqing County, north Beijing, where the first National Geologic Park of Petrified Wood of China has been built since 2002. A few trunks have well‐preserved growth rings. One petrified stump from the formation shows a positive phototropism direction of SW230°. As compared with the modern normal gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The first author of this paper found that the tree rings of the in situ preserved silicified trunks are clear and characterized by the obvious asymmetry in the SW 220 sides. Compared with the living trees phototropism [6], the result is almost the same. This means that the positive phototropism the trees are in accordance with the present ones, and possibly indicating that the Junggar basin has never rotated since the Late Jurassic.…”
Section: Orientation Of the In Situ Preserved Silicified Trunk And Romentioning
confidence: 77%
“…The first author of this paper found that the tree rings of the in situ preserved silicified trunks are clear and characterized by the obvious asymmetry in the SW 220 sides. Compared with the living trees phototropism [6], the result is almost the same. This means that the positive phototropism the trees are in accordance with the present ones, and possibly indicating that the Junggar basin has never rotated since the Late Jurassic.…”
Section: Orientation Of the In Situ Preserved Silicified Trunk And Romentioning
confidence: 77%
“… No. Formation GPS position locality Dominant Eccentricity The other largest outermost directions TJS 1 the Tiaojishan Formation 41°27′30″N, 120°47′13″E Beipiao of western Liaoning province 233° 305° TJS 2 the Tiaojishan Formation 41°27′30″N, 120°47′12″E Beipiao of western Liaoning province 247° No TJS 3 the Tiaojishan Formation 41°21′30″N, 120°47′12″E Beipiao of western Liaoning province 230° No TCZ 1 the Tuchengzi Formation 40°42′4.1″N, 116°25′15.399″E Yanqing of Beijing 230° No TCZ 2 (modified from reference 34 —Jiang et al ., 2014) the Tuchengzi Formation 40°42′5.301″N, 116°28′15.44″E Yanqing of Beijing 235° No TCZ 3 the Tuchengzi Formation 40°42′5.362″N, 116°23′16.452″E Yanqing of Beijing 236° 44° TCZ 4 the Tuchengzi Formation 40°42′6.023″N, 116°23′17.07″E Yanqing of Beijing 233° No Note: TJS = Tiaojishan TCZ = Tuchengzi. …”
Section: Resultsmentioning
confidence: 99%
“…In the Northern Hemisphere, trunk phototropism is observed at high latitudes and extends south to at least the Tropic of Cancer (N23°26′) 34 . The magnitude of the phototropic response generally varies from stronger at the poles to weaker at the lower latitudes, finally disappearing near the tropics 34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations